(untitled) (Annals of Medical Research, 2023)
Aim: Our aim was to investigate the relationship between common geriatric syndromes and depression. Materials and Methods: 515 patients over 65 years old admitted to a university hospital participated in this cross-sectional study. The Beck Anxiety Inventory (BAI), the European Quality of Life (EQ-5D), and the Pittsburgh Sleep Quality Index (PSQI) were administered to the participants in addition to the Comprehensive Geriatric Assessment. The Geriatric Depression Scale (GDS) was used to assess depressive symptoms in persons 65 years and older. Results: The mean age of the participants was 72.2±6.3 years, and 133 (24.8%) of them scored high on the GDS for depression. The non-depressed group had lower rates of sarcopenia, fewer medications, lower BAI and PSQI scores, and higher EQ-5D and Instrumental Activities of Daily Living (IADL) scores. Correlation analysis showed that the GDS score was moderately positively associated with the number of medications (r = 0.351, p = <0.001), the BAI score (r = 0.638, p = <0.001), and moderately negatively associated with the IADL score (r = -0.355, p = <0.001) and the Mini Nutritional Assessment (MNA) score (r = -0.316, p = <0.001). After multivariate logistic regression analysis, IADL, MNA, and BAI scores were independently associated with depression (p = 0.026, OR = 0.72, p = 0.026, OR = 0.94, and p = <0.001, OR = 1.11, respectively). Conclusion: Interventions aimed at alleviating depressive symptoms may be an effective strategy for preventing the adverse consequences of depression that lead to deterioration in quality of life. Therefore, focusing on factors that are independently associated with depression, such as dependency in activities of daily living, anxiety symptoms, and poor nutritional status, may be a useful method in the management of older patients with depression.